2018
DOI: 10.1111/rode.12402
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of interest rates in microfinance: Age, scale and organizational charter

Abstract: This study compares the responsiveness of microcredit interest rates with age, scale of lending, and organizational charter. It uses an unbalanced panel of 300 microfinance institutions (MFIs) from 107 developing countries from 2005 to 2015. Three key trends emerge from the results of a 2SLS regression. First, the adoption of formal microbanking practices raises interest rates compared with other forms of microlending. Second, large‐scale lending lowers interest rates only for those MFIs that already hold lega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This attests to the female vulnerability to poverty as described by Bhatt and Tang (2005). Against this backdrop, we fittingly employ 'Percentage of female borrowers' (pfb) as another proxy for depth of outreach to reflect a segment of the deprived population (Nwachukwu et al 2018). The use of this variable is vital in this study as it is reported that although women play an important role in Ghanaian agriculture, they experience productivity constraints due to the lack of or limited access to credits and land (Gbedemah, Jones, and Pereznieto 2010).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…This attests to the female vulnerability to poverty as described by Bhatt and Tang (2005). Against this backdrop, we fittingly employ 'Percentage of female borrowers' (pfb) as another proxy for depth of outreach to reflect a segment of the deprived population (Nwachukwu et al 2018). The use of this variable is vital in this study as it is reported that although women play an important role in Ghanaian agriculture, they experience productivity constraints due to the lack of or limited access to credits and land (Gbedemah, Jones, and Pereznieto 2010).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Kapkiyai and Kimitei (2015) asserted that the interest rate applied is contingent upon the borrower's risk profile, serving to mitigate adverse selection issues that arise when distinguishing between non-risky and risky borrowers. According to standard economic theory, the reduced interest rates are the result of cost reductions brought on by experience, learning through experience, and economies of scale Nwachukwu et al (2018). Additionally, interest rates may exhibit discrimination between female and male borrowers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most microfinance institutions have succeeded to develop and create sustainable activities by applying interest rates that cover their overall operating costs ( Rosenberg et al, 2009 ; Gupta and Mirchandani, 2019 ). The interest rate variation comes out of several factors that are less manageable by micro-credits ( Nwachukwu et al, 2018 ). There are also micro-credits whose activities are only motivated by profit-seeking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these limitations, these works have not highlighted the MFI legal status effects and the impact of female borrowers on interest rate fluctuations ( Nwachukwu et al, 2018 ). This article removes these ambiguities by using the Fisher hypothesis test and by showing the threshold at which the share of women in microfinance institutions has a fluctuating impact on the rate of interest.…”
Section: Introductionmentioning
confidence: 99%